PENGARUH FAKTOR KEPUASAN KERJA TERHADAP PRESTASI KERJA KARYAWAN BAGIAN OPERASINAL PADA PT SEMEN TONASA (PERSERO) KABUPATEN PANGKEP - Andi Alif Haeruddin; Amiruddin Tawe; Nurman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine the influence of job satisfaction factors on work performance of employees in the operational division of PT Semene Tonasa, Pangkep Regency. The population in this study were all employees of the operational division, while the sample in this study consisted of approximately 100 people. Data collection techniques were carried out using a questionnaire. . Data analysis techniques were carried out using quantitative analysis using the SPSS application. The data obtained from the research results will be compared with the existing theory in this study. The results of this study indicate that the factors of job satisfaction namely the work itself, salary, work environment simultaneously have a significant effect on employee performance and partially the work itself has an effect but not significant while salary and work environment have a significant effect on employee performance. The correlation coefficient of 0.671 is in the interval 0.60-0.799 which indicates the strength of the relationship between the independent variable and the dependent variable is strongly correlated. The coefficient of determination of 0.450 indicates the independent variable to predict the dependent variable of 45.0%, the remaining 55.0% is influenced by other factors.